Association between sarcopenia components and depressed mood varies by sex among community-dwelling older adults from the Korean Frailty and Aging Cohort Study - Yong Soon Park; Keunjoong Yoo; Hye Jin Kim; Miji Kim; Chang Won Won (Scientific Reports)
Abstract This cross-sectional study investigated the association between sarcopenia components and depressed mood in community-dwelling adults aged 70–84 years from the Korean Frailty and Aging Cohort Study. Depressed mood was assessed using the Geriatric Depression Scale short form. Logistic regression was used to examine sex-specific associations between sarcopenia components and depressed mood. Among 1,913 participants (mean age: 75.9 years, 49.0% women), 12.2% and 23.6% had depressed mood and sarcopenia, respectively. Sarcopenia prevalence increased among individuals with depressed mood in both sexes (men: P < 0.001; women: P = 0.016). Severe sarcopenia (men: OR, 3.620; 95% CI, 1.634−8.022; women OR, 3.332; 95% CI, 1.689−6.574) and concurrent low muscle strength and physical performance (men: OR, 3.660; 95% CI, 1.541−8.691; women: OR, 2.333; 95% CI, 1.294−4.206) correlated with depressed mood across sexes. The co-occurrence of low muscle mass and muscle strength (OR, 2.451; 95% CI, 1.007−5.964) was associated with depressed mood in men, whereas low physical performance (OR, 2.007; 95% CI, 1.275−3.160) and the coexistence of low muscle mass and physical performance (OR, 1.804; 95% CI, 1.003–3.248) correlated with depressed mood in women. Sarcopenia and depressed mood were significantly associated among older adults, underscoring the need to account for sex-specific differences in sarcopenia components when evaluating mental health outcomes to tailor interventions targeting sarcopenia and improve the mental well-being of aging populations.